Hypersensitivities: An unexpected response of the Immune System with pathological consequences - Moreno-Correa, Sandra (2019)
Hypersensitivities aredefined as exaggerated responses of the immune system to antigens that can be exogenous or endogenous, innocuous or infectious. This type of responses triggers pathological inflammatory manifestations in the tissue in which it takes place. They are classified into 4 types, I, II, III and IV, depending on the type of mediator, the type of antigen that induces the reaction and the effector mechanism. Understanding the pathophysiological mechanisms involved in this type of responses is very important to understand the role of the Immune System in pathological processes and how precisely the System of defenses of the organism can be involved in the damage to one’s own, to apply said knowledge to the understanding and management of related pathologies. This class note is the product of an activity carried out in the course of infections and immunity called Wiki and is constituted in a collaborative text constructed among all the participants that favored the learning process of the subject of hypersensitivities.